2016
DOI: 10.1093/femsec/fiw164
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis and adherence to fungal surfaces are key components of the behavioral response ofBurkholderia terraeBS001 to two selected soil fungi

Abstract: Burkholderia terrae BS001 has previously been proposed to be a 'generalist' associate of soil fungi, but its strategies of interaction have been largely ignored. Here, we studied the chemotactic behavior of B. terrae BS001 towards Lyophyllum sp. strain Karsten and Trichoderma asperellum 302 and the role of fungal surface molecules in their physical interaction with the bacteria. To assess the involvement of the type 3 secretion system (T3SS), wild-type strain BS001 and T3SS mutant strain BS001-ΔsctD were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
(89 reference statements)
1
22
2
Order By: Relevance
“…In a recent paper, we provide the arguments for a focus on CMHs as dynamic molecular ‘rafts’ that can become surface-exposed in fungal hyphae (Haq et al, 2016). We thus questioned the putative role of such CMH ‘anchors’ as sites for attachment of mycosphere bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, we provide the arguments for a focus on CMHs as dynamic molecular ‘rafts’ that can become surface-exposed in fungal hyphae (Haq et al, 2016). We thus questioned the putative role of such CMH ‘anchors’ as sites for attachment of mycosphere bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…From the bacterial side, a role for the type 3 secretion system (T3SS) and/or for type 4 pili has been proposed (Yang et al, 2016). However, there has so far been no clue as to the existence of any dedicated ‘receptor’ site at the fungal cell surface, even though Haq et al (2016) recently found evidence for the presence of ceramide monohexosides (CMH) as molecular ‘rafts’ in the cell surface of Trichoderma asperellum 302. In previous studies, we have reported the finding of biofilm-like structures (cell agglomerates) consisting of B. terrae BS001 cells at the hyphae of Lyophyllum sp.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 gives an impression of the stimulatory effects of soil fungi on hypha-associated bacteria. The end result is often an enhanced spatial proximity between the local cell populations, which may culminate in the formation of biofilms or similar aggregations (Berthold et al 2016;Haq et al 2016). In theory, such enhanced cell-to-cell proximity, equivalent to raised cell densities (expressed per unit soil volume) will enhance the frequencies of (genetic) interactions between the cells.…”
Section: Cell-to-cell Interactionsmentioning
confidence: 99%
“…hospita cluster) have been encountered as prime and consistent colonizers of fungal tissue in soil. In a key laboratory study, Haq et al (2016) recently provided evidence for the high affinity and chemotactic movement of one such organism, P. terrae BS001, toward the hyphae of the soil saprotrophs Lyophyllum sp. strain Karsten and Trichoderma asperellum.…”
Section: Selection Of Fungal-associated Bacteria In Particularmentioning
confidence: 99%
See 1 more Smart Citation